Personal injuries - Turow, Scott (New York : Farrar, Straus and Giroux, 1999)
An FBI operation is held to catch a group of corrupt judges in high places. The central figure is a crooked lawyer who bribed judges on his cases. Nabbed by the IRS for tax evasion, he agrees to be wired and serve as bait in return for a reduced sentence.
Map of Kindle County, USA on endpapers.
Keywords: Kindle County (Imaginary place) -- Fiction; Condado de Kindle (Lugar imaginario) -- Ficción.; Legal stories